PROCUREMENT MANAGEMENT AS A CONDITION OF INCREASING THE COMPETITIVENESS OF AGRO-PROCESSING ENTERPRISES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The authors systematized approaches to the essence of the categories “product competitiveness”, “enterprise competitiveness”, “field competitiveness”, “regional competitiveness” and “country competitiveness”. The authors formulated the definition of competitiveness. The approaches to the classification of competitiveness factors are systematized. The authors’ classification of factors was developed. The authors have proved that the main factor in the competitiveness of enterprises is raw materials. Obtaining raw materials by the enterprise is carried out through procurement. Thus, the management of procurement of goods, having the largest share in the cost of the final product, is the main factor affecting the competitiveness of the enterprise. The authors have systematized approaches to characterizing the essence, goals and objectives of procurement management and to the classification of purchases. The authors’ definition of procurement management and the composition of its principles are proposed. The mechanisms of influence on the management of procurement and processing enterprises of the agro-industrial complex are investigated on the example of the open joint-stock company “Pukhovichi Plant of Grain Products” (Belarus). Possible ways to improve the procurement management of the studied organization are proposed. The recommendations proposed by the authors can be used by other organizations of the processing industry of the agro-industrial complex.